Postnatal Development of Subcallosal Zone Following Suppression of Programmed Cell Death in Bax-deficient Mice - Kim, Woon Ryoung (Dev Reprod, 2013)
Neural stem cells are found in adult mammalian brain regions including the subgranular zone (SGZ) of the dentate gyrus (DG) and the subventricular zone (SVZ). In addition to these two regions, other neurogenic regions are often reported in many species. Recently, the subcallosal zone (SCZ) has been identified as a novel neurogenic region where new neuroblasts are spontaneously generated and then, by Bax-dependent apoptosis, eliminated. However, the development of SCZ in the postnatal brain is not yet fully explored. The present study investigated the precise location and amount of neuroblasts in the developing brain. To estimate the importance of programmed cell death (PCD) for SCZ histogenesis, SCZ development in the Bax-knockout (KO) mouse was examined. Interestingly, an accumulation of extra neurons with synaptic fibers in the SCZ of Bax-KO mice was observed. Indeed, Bax-KO mice exhibited enhanced startle response to loud acoustic stimuli and reduced anxiety level. Considering the prevention of PCD in the SCZ leads to sensory-motor gating dysfunction in the Bax-KO mice, active elimination of SCZ neuroblasts may promote optimal brain function.